Twentieth-century German political thought - Stirk, Peter M. R., 1954- (Edinburgh University Press, 2006)
Germany, as Europe's most powerful state, has a political significance which underlines the importance of twentieth-century German political thought. Yet this tradition has been poorly represented in academic literature. This book offers: an account of German political thought emphasising its diversity and contested nature an overview of the subject that allows access to relatively unknown figures as well as the 'names' of the tradition (Weber, Schmitt, Arendt, Habermas) a demonstration of the political significance of figures better known in other disciplines including law and sociology The book is organised chronologically, with a series of recurrent themes providing analytic unity: (i) the nature of politics (including political vocation and leadership, and definitions of politics), (ii) collective identity, (iii) the rule of law, (iv) the role of the state, (v) the role of political parties and the nature of parliamentary democracy, (vi) state intervention in society and the economy, and (vii) the international order. Pedagogical features include a glossary of German terms and a substantial set of biographical notes identifying the major theorists referred to in the text. Key Features: Challenges established perceptions by presenting German political thought as a contested tradition Presents a rich picture of German political thought by covering a wide range of theorists Its broad chronological range provides the first overview of 20th-century German political thought in one volume